Food security and the functioning of wheat markets in Eurasia: A comparative price transmission analysis for the countries of Central Asia and the South Caucasus - Miranda Svanidze; Linde Johanna Götz; Ivan urić; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2019)
We investigate wheat price relationships between the import-dependent countries in Central Asia and the South Caucasus and the Black Sea wheat exporters to assess wheat market efficiency which is crucial for ensuring availability and access to wheat and for reducing food insecurity. Results of linear and threshold error correction models suggest strong influence of trade costs on market integration in Central Asia, while those costs are of minor importance in the South Caucasus. In particular, wheat trade in Central Asia is characterized not only by higher transportation costs but also unofficial payments play a large role. In addition, wheat price volatility is substantially higher in the wheat importing countries of Central Asia compared to the South Caucasus. To foster market functioning, wheat trade should be facilitated by policies reducing trade costs. This includes investments in grain market infrastructure, eliminating unofficial payments, but also resolving geopolitical conflicts. However, wheat trade in this region is characterized by large distances, low scope for import diversification and repeated export restrictions by Black Sea exporters. Therefore, trade enhancing policies should be complemented with policies increasing wheat self-sufficiency to enhance food security.
urn:nbn:de:gbv:3:2-107209
Keywords: 330; price transmission; wheat market integration; transportation costs; food security; Central Asia; the South Caucasus